Effect of the Geological Situation of the Late Jurassic-Early Cretaceous Period of the Region between the Upper and Lower Zab Rivers on the Oil Potential of the Najmah Formation-North Iraq - العيسى, د. مروان ادريس سلطان (Journal of Petroleum Research and Studies, 2021)
To determine the location of the faults and the extent of their impact, a comparison made between the subsurface sections of the upper regions to determine the sites of the faults and their impact as: • The Fault Z1 is determined by the location of the upper Zab River, Fault Z2, was represents the Lower Zab River and the Fault Z3, extending northwest southeast and is located between the well sites of Zab-1 and Quwer-2. This fault fragmented of the inter Zab rivers area into two secondary blocks, the Western sub-block and a Eastern sub-block, where this was 500 meters lower than the first one and forming a good Structural trap. The effect of those Normal faults (1Z, 2Z, 3Z), was perfectly limited on the Late Jurassic-Early Cretaceous boundary. Which revealed that the reservoir unit (Najmah formation), was exposed to the surface and the cap rocks have been eroded by the Neocomian uplift, and lading to escape of the light hydrocarbon components while the heavy bituminous stained the lithofacies and plugged their porosity